An Analysis of Indonesian - English Code Mixing in Kompas Daily Newspaper - Sri Hardianti Margareta; Bukhari Daud; Burhansyah Burhansyah (Research in English and Education Journal, 2019)
This research study investigates about the code-mixing of Indonesian and English used by the journalist in explaining the news. In this research, the writer used the Kompas daily newspaper as the data. Mass media is believed to present information often use the foreign vocabulary by doing code mixing to make the writing become more interesting and modern. The aim of this study is to find the types of code mixing used in the Kompas Daily Newspaper using Musyken’s (2000) theory, who proposes : Insertion, Alternation, and Congruent Lexicalization, and in the form of words and phrases code mixing. The text selected for analysis was obtained from the editions 2nd January to 14th January 2018, and the column were taken from the headlines of Economics (Business) and Politics (Law). In collecting the data, the researcher used documentation analysis involving note takes of the occurances of English code mixing in the selected articles. The data obtained were classified using classification table. The findings show numerous code mixing cases being used in the stated articles.The result showed that the most frequently type of code mixing used in Kompas Daily Newspaper is insertion.  Meanwhile, the factor of code mixing use in Kompas Daily Newspaper are because of terminology that can’t be translated that have a particular meaning, Emphasis the meaning of word and untranslatable that have a match in Indonesia Language.